2019
DOI: 10.1101/752147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sugar availability suppresses the auxin-induced strigolactone pathway to promote bud outgrowth

Abstract: +33 (0)2 41 22 56 32 2 SUMMARY• Apical dominance occurs when the growing shoot tip inhibits the outgrowth of axillary buds. Apically-derived auxin in the nodal stem indirectly inhibits bud outgrowth via cytokinins and strigolactones. Recently, sugar deprivation was found to contribute to this phenomenon.• Using rose and pea, we investigated whether sugar availability interacts with auxin in bud outgrowth control, and the role of cytokinins and strigolactones, in vitro and in planta.• We show that sucrose antag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…Sucrose has been shown to promote axillary bud outgrowth and alleviate the inhibitory effect of SL during this process in dicotyledonous models 21,26 . However, this antagonistic interaction has not been reported in monocotyledons plants, which have an architecture different compared with eudicots.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sucrose has been shown to promote axillary bud outgrowth and alleviate the inhibitory effect of SL during this process in dicotyledonous models 21,26 . However, this antagonistic interaction has not been reported in monocotyledons plants, which have an architecture different compared with eudicots.…”
Section: Resultsmentioning
confidence: 99%
“…In this species, decapitation triggers bud outgrowth through redistribution of sugars towards axillary buds, and sucrose feeding can trigger bud release 7,8 . To explore whether a similar mechanism for sucrose regulation of gene expression may occur in pea, we examined the expression of PsD3 and PsD14 in pea as well as their downstream target BRC1 , the orthologue of TB1 8,25,26 in response to sucrose feeding and decapitation. Similar to the result observed for D3 in rice in response to sucrose, decapitation led to a decrease in PsD3 and BRC1 expression but not in PsD14 (Figure 7a-c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an elegant set of experiments, Mason et al (2014) demonstrated the systemic movement of sucrose as a branching signal from the leaf to the lateral bud after decapitation. Barbier et al (2015a) demonstrated that sugar availability, together with auxin (Bertheloot et al, 2019), control the entrance of buds into sustained growth. Recently, we showed that sucrose and its hydrolytic products can induce stem branching in a dose-responsive manner under etiolated conditions (Salam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose has been reported to strongly induce CK synthesis in in vitro -grown single nodes of rose in absence of auxin, suggesting that CKs might mediate the effect of sucrose, although the authors concluded that CKs alone are not sufficient to stimulate bud outgrowth in Rosa single nodes (F. Barbier et al, 2015). In presence of auxin in the growth medium, sucrose could not promote CK accumulation, and the CK content did not correlate with the onset of bud outgrowth (Bertheloot et al, 2019). Here, we report here that CKs play an important role in mediating sucrose-promoted bud outgrowth in etiolated potato stem.…”
Section: Discussionmentioning
confidence: 99%